Urgensi Penerapan Nilai-nilai Etika Bisnis Kristen Dalam Rekrutmen Ketenagakerjaan - Elia, Samuel; Simanjuntak, Ferry (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
Business Ethics as part of life has an important role, therefore it requires a proper understanding based on the correct values. Business Ethics with a Christian perspective can provide proper guidance for the lives of believers. Especially Christian business people or other related parties. This research uses a qualitative method, namely research based on various literature studies. Based on the existing opinions and theories, the result is that the implementation of the Christian Business Ethics perspective in recruitment activities does not only touch the spiritual aspect, but also contains professional values for the greater interest, such as avoiding deviant policies such as Corruption. Collusion-Nepotism (KKN) and discrimination – favoritism, and uphold the value of professionalism (expertise, skills and knowledge) in order to achieve performance and productivity for the common good.